Electron deficiency in tetrahedral transition-metal clusters: Electronic structure and magnetic properties of [Ru-4(eta(6)-C6H6)(4)(mu(3)-H)(4)](2+) - Gautier, Régis; Cherioux, Frédéric; Süss-Fink, Georg; Saillard, Jean-Yves (My University, 2003)
Analysis of the electronic structure of the electron-deficient cluster cation [Ru-4(eta(6)-C6H6)(4)H-4](2+) (1(2+)) by density functional theory calculations shows a very small energy gap (0.06 eV) between the diamagnetic singlet state and the paramagnetic triplet state, as a consequence of the absence of a significant Jahn-Teller distortion in the molecular structure of 1(2+). Magnetic measurements of [1]Cl-2, [1][BF4](2), and [1][PF6](2) show 1(2+) to be diamagnetic in the fundamental state, with some weak temperature-independent paramagnetism, depending upon the nature of the counterion.
Keywords: NUMERICAL-INTEGRATION; RUTHENIUM COMPLEXES; HYDROGEN ACTIVATION; CRYSTAL-STRUCTURE; AQUEOUS-SOLUTION; ENERGY; APPROXIMATION; LIGANDS; IRIDIUM